Fabrication and characterization of electrospun psyllium husk‐based nanofibers for tissue regeneration. Issue 24 (12th February 2021) - Poddar, Suruchi; Agarwal, Piyush Sunil; Sahi, Ajay Kumar; Varshney, Neelima; Vajanthri, Kiran Yellappa; Mahto, Sanjeev Kumar
Abstract: The present study reports for first time the blending of psyllium husk (PH) powder/gelatin (G) in the polymer‐rich composition of polyvinyl alcohol (PVA) to make an electrospinnable solution. The composite was prepared in 3 different ratios viz., 100% (wt/wt) (PVA + PH), 75% + 25% (PVA + 75PH + 25G) (wt/wt) and 50% + 50% (PVA + 50PH + 50G) (wt/wt) in 6% PVA solution. Optimum electrospinning parameters were evaluated for all the prepared blends. The fabricated nanofibers were characterized by scanning electron microscopy (SEM), attenuated total reflectance‐Fourier transform infrared, differential scanning calorimetry, porosity percentage, and fiber orientation using ImageJ software. A qualitative in vitro degradation study at room temperature is supported by SEM images. The cellular interactions were characterized by MTT assay of NIH‐3T3 fibroblast cells for 2 and 4 days with an optimum cell growth of >50% by fourth day of culture and long‐term cultivation of L929‐RFP cells was observed for 10 days. The nanofibers were formed in the range of 49–600 nm. PVA + 75PH + 25G when cultured with L929‐RFP cells exhibited highest fluorescence intensity and thus supported cellular proliferation significantly. Based on the results obtained from various analyses, we anticipate that fabricated psyllium‐based nanofiber can be used as a promising candidate for wound healing and other biomedical applications. Abstract :